2004
DOI: 10.1002/jcu.20047
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral epidermoid cysts of the testis: Sonographic and MRI findings

Abstract: Epidermoid cysts of the testis are rare benign lesions, without malignant potential, that can be managed conservatively with cyst enucleation and testis-sparing surgery. Bilateral epidermoid cysts in the testes have been reported very infrequently. We report the sonographic and MRI findings in a patient who presented with a palpable nodule in only 1 testis, but in whom sonography showed bilateral lesions. On sonography, the cysts had an internal "onion-ring" structure; color Doppler signals were absent. On MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…It has been reported that most tumors larger than 1.6 cm show internal color Doppler signals 23 and that a lack of internal vascularity in tumors of this size is more suggestive of benign lesions. 7 However, none of the teratomas in our series, including 2 that were 2.5 and 1.8 cm, respectively, in diameter, showed blood flow on color or power Doppler examinations.…”
contrasting
confidence: 51%
“…It has been reported that most tumors larger than 1.6 cm show internal color Doppler signals 23 and that a lack of internal vascularity in tumors of this size is more suggestive of benign lesions. 7 However, none of the teratomas in our series, including 2 that were 2.5 and 1.8 cm, respectively, in diameter, showed blood flow on color or power Doppler examinations.…”
contrasting
confidence: 51%
“…(1,2) Bilateral testicular epidermoid cysts are even rarer, and to our knowledge, only 15 patients have been reported in the English literature. (3)(4)(5)(6) Multiple cysts have been reported in patients with Gardner syndrome, Klinefelter syndrome and cryptorchid testes. (7,8) The age of affected patients range from 3 to 77 years, with the majority in the second to fourth decades of life.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral TEC is a very rare condition, with only a few reports in the literature. [1619] In all, pre-operative imaging suggested the correct diagnosis and testis-preserving surgery, using enucleation or wedge resection, was performed for most of the involved testes. Bilateral TEC presents a unique challenge in treatment as the previously accepted protocol would entail bilateral orchiectomy.…”
Section: Discussionmentioning
confidence: 99%